The effect of permanent shade tree at mature tea area on microclimate, the population of pest insects and natural enemies, and tea shoot production - Widayat, Wahyu; Rayati, Dini Jamia (Jurnal Penelitian Teh dan Kina, 2011)
A study to know the effect of permanent shade trees at mature tea area on microclimate, the population of pest insects and natural enemies, as well as tea shoot production was carried out at Blok B-4 Afdeling Gambung Selatan (1.300 m asl) of Research Insitute for Tea and Cinchona, Bandung, West Java, from January up to December 2009. The study carried out using experimental observation method with two treatments, viz. mature tea area with and without permanent shade tree, silver oak (Grevillea robusta). The parameters of microclimate: temperature, relative humidity, and sunshine intensity, the population of various pest insects and natural enemies, as well as tea shoot production were observed regularly during dry and rainy seasons at the two experimental plots. The results showed that the existence of permanent shade trees Grevillea robusta at mature tea area could maintain the temperature, relative humidity (RH), and sunshine intensity suitable for tea growth at dry season, suppress the population of pest insects, and on the contrary increase the population of natural enemies, as well as increaseÂ  the tea shoot production, up to 21% at rainy season, and up to 55% at dry season.